Prevalence and intensity of helminth parasites in Mystus tengara - Begum, Aleya; Sehrin, Subrina; Sultana, Yasmin; Mahmood, Nurul Arefin (Dhaka University Journal of Biological Sciences, 2015)
Abstract not available Dhaka Univ. J. Biol. Sci. 24(1): 107-110, 2015 (January)